The influence of the polar head-group of synthetic cationic lipids on the transfection efficiency mediated by niosomes in rat retina and brain. (January 2016) - Ojeda, E.; Puras, G.; Agirre, M.; Zarate, J.; Grijalvo, S.; Eritja, R.; Martinez-Navarrete, G.; Soto-Sánchez, C.; Diaz-Tahoces, A.; Aviles-Trigueros, M.; Fernández, E.; Pedraz, J.L.
Abstract: The development of novel non-viral delivery vehicles is essential in the search of more efficient strategies for retina and brain diseases. Herein, optimized niosome formulations prepared by oil-in water (o/w) and film-hydration techniques were characterized in terms of size, PDI, zeta potential, morphology and stability. Three ionizable glycerol-based cationic lipids containing a primary amine group (lipid1 ), a triglycine group (lipid2 ) and a dimethylamino ethyl pendent group (lipid3 ) as polar head-groups were part of such niosomes. Upon the addition of pCMS-EGFP plasmid, nioplexes were obtained at different cationic lipid/DNA ratios (w/w). The resultant nioplexes were further physicochemically characterized and evaluated to condense, release and protect the DNA against enzymatic digestion. In vitro experiments were performed to evaluate transfection efficiency and cell viability in HEK-293, ARPE-19 and PECC cells. Interestingly, niosome formulations based on lipid3 showed better transfection efficiencies in ARPE-19 and PECC cells than the rest of cationic lipids showed in this study. In vivo experiments in rat retina after intravitreal and subretinal injections together with in rat brain after cerebral cortex administration showed promising transfection efficiencies when niosome formulations based on lipid3 were used. These results provide new insights for the development of non-viral vectors based on cationic lipids and their applications for efficient delivery of genetic material to the retina and brain.